Analysis of Financial Market in Malaysia Using ARCH and GARCH-Type Model - Chu, Wei Hao; Saharan, Sabariah (Enhanced Knowledge in Sciences and Technology, 2024)
The stock market is a platform for investors to buy and sell shares of ownership incompanies. The foreign exchange market is a global decentralized marketplace forindividuals and businesses to trade currencies for international investment. In this study,ARCH and GARCH models was apply to analyze the volatility from both the bankingstock such as CIMB, Maybank and Public Bank and Forex markets, MYR/USD.Parameters such as Log Likelihood (LL), Akaike Info Criterion (AIC), Schwarz Criterion(SC) and Hannan-Quinn Criterion (HQC) will used to compared the ARCH and GARCHmodel. Moreover, adjusted R-Squared (ARS), standard error regression (SER) and sumsquared residual (SSR) will be used to decide the most volatile market within the ARCHand GARCH model. Next, calculating simple return rates is to identify the return rates forstock and Forex market. Based on the result, Forex market (MYR/USD) is much morevolatile than the stock market (CIMB, Maybank and Public Bank). This indicate that theprices of currencies can fluctuate more rapidly than the prices of the stocks. However,stock market has higher return than the forex market. This means that investors can expectto make more money over the long term by investing in stocks than by investing incurrencies. The personal choice of investing in either stock or Forex market depends onthe individual risk tolerance.